Design and characterization of a cheese spread incorporating osmundea pinnatifida extract - Faustino, Margarida (2023)
Marine algae have been emerging as natural sources of bioactive compounds, such as soluble dietary fibers and peptides, presenting special interest as ingredients for functional foods. This study developed a cheese spread incorporating red seaweed Osmundea pinnatifida extract and subsequently characterized it in terms of nutritional, pH, and microbiological parameters and bioactivities including prebiotic, antidiabetic, antihypertensive, and antioxidant activities. This food was produced through incorporation of O. pinnatifida extract (3%), obtained via enzymatic extraction Viscozyme L in a matrix containing whey cheese (75%) and Greek-type yoghurt (22%). The product was then subjected to thermal processing and subsequently stored for 21 days at 4 °C. During storage, this food showed a high pH stability (variations lower than 0.2 units), the absence of microbial contamination and all tested bioactivities at the sampling timepoints 0 and 21 days. Indeed, it exerted prebiotic effects under Lactobacillus acidophilus LA-5® and Bifidobacterium animalis subsp. lactis BB-12®, increasing their viability to around 4 and 0.5 log CFU/g, respectively. In addition, it displayed antidiabetic (α-glucosidase inhibition: 5–9%), antihypertensive (ACE inhibition: 50–57%), and antioxidant (ABTS: 13–15%; DPPH: 3–5%; hydroxyl radical: 60–76%) activities. In summary, the cheese spread produced may be considered an innovative food with high potential to contribute toward healthier status and well-being of populations.